Proven Cases of Duodenal Atresia on Plain Abdominal Radiography in Correlation With Surgical Findings : a Cases Series - Fiona Fiona; Ni Nyoman Margiani; Firman Parulian Sitanggang (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2020)
Duodenal atresia is an emergency congenital abnormality and the most common cause of proximal bowel obstruction in neonates, where the duodenum has not developed properly in embryogenesis with a blind end that cannot be seen through gastric contents. The incidence of duodenal atresia is 1/10,000 live births that commonly affecting boys than girls. In cases of neonatal bilious vomiting, the first choice imaging modality is plain abdominal radiography. The purpose of this case report is to increase radiologist and pediatrician awareness in duodenal atresia diagnosis through plain abdominal radiography and to minimize radiation in the neonates. We report 3 cases of duodenal atresia that were found in Sanglah Hospital, Denpasar in 1 year for the period 2018 - 2019. Case 1: A 4-day-old baby girl presented with bilious vomiting in the first 24 hours after birth. Case 2: A 4-day-old baby boy presented with lethargic, weak crying and groaning after birth. There is no history of passed meconium in the first 24 hours of birth. Case 3: A newborn boy presented with bilious emesis after breastfeeding and non projectile. From the 3 cases, a plain abdominal radiograph was examined and a double bubble sign with no intestinal gas distal was found.